1997
DOI: 10.1038/bjc.1997.195
|View full text |Cite
|
Sign up to set email alerts
|

Expression and hormone regulation of Wnt2, 3, 4, 5a, 7a, 7b and 10b in normal human endometrium and endometrial carcinoma

Abstract: Summary Wnt genes are transforming to mouse breast epithelium and are hormonally regulated in vivo. To assess their role in another endocrine-responsive human cancer, the expression of seven Wnt genes (Wnt 2, 3, 4, 5a, 7a, 7b and 1 Ob) in normal human endometrium and endometrial cells, and endometrial carcinoma tissues and cell lines was investigated by ribonuclease protection analysis. Wnt2, 3, 4 and 5a mRNAs but not Wnt7a, 7b or 10b mRNAs were expressed in primary culture of normal endometrial epithelial (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
96
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 25 publications
(17 reference statements)
8
96
1
2
Order By: Relevance
“…This contrasts with our studies of breast (Huguet et al, 1994) and endometrial (Bui et al, 1997a) cancer where wnts 5a, 7b and 10b, but not wnt 2, were up-regulated. It may be that several wnt genes are involved in the growth and development of individual organs and each cancer type may exhibit a deregulation in the expression of one or more wnt genes controlling normal development within that organ.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts with our studies of breast (Huguet et al, 1994) and endometrial (Bui et al, 1997a) cancer where wnts 5a, 7b and 10b, but not wnt 2, were up-regulated. It may be that several wnt genes are involved in the growth and development of individual organs and each cancer type may exhibit a deregulation in the expression of one or more wnt genes controlling normal development within that organ.…”
Section: Discussioncontrasting
confidence: 99%
“…Wnt genes were initially isolated from mouse mammary carcinomas by insertional mutagenesis, but we have shown that they are also up-regulated in human hormone-dependent cancers of the breast (Huguet et al, 1994) and endometrium (Bui et al, 1997a). Wnts are members of a multigene family with over 14 genes in humans and most are conserved in Xenopus, suggesting specialized roles for each gene product.…”
Section: Discussionmentioning
confidence: 99%
“…Among them seven genes have been reported previously as differentially expressed in endometrial tumors. Lactotransferrin (LTF) was upregulated (Walmer et al, 1995), whereas six genes including SFRP4, DCN, IGFBP6, HGF, WT1 and WNT4 were downregulated in the endometrial tumors (Rutanen et al, 1994;Bui et al, 1997;Yoshida et al, 2002;Muller-Tidow et al, 2003;Smid-Koopman et al, 2004;Acs et al, 2004;Hrzenjak et al, 2004). Of these genes, only WT1 was been specifically associated with endometrioid cancer (Acs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One model is that the primary role of PR during very early differentiation is to modulate expression levels of target gene transcription rather than act as an all or none regulator. Known target genes of PR in mature tissues that we examined in our study include Wnt4, Wnt5b and Areg, all of which are important developmental genes [50][51][52][53][54][55][56]. None of these known PR target genes are regulated by treatment with progesterone or the antiprogestin RU486 in mES cells.…”
Section: Discussionmentioning
confidence: 99%
“…We examined PR expression itself, since it has been reported to be down regulated by progesterone in some tissues [49]. We also examined the levels of expression of three genes that have been shown to be regulated by progesterone in mature tissues: Wnt4, Wnt5b, and amphiregulin (Areg) [50][51][52][53][54][55][56]. As can be seen in Figure 6, all four of these genes showed virtually no expression in undifferentiated mES cells (+LIF) and there was no effect of progesterone nor RU486 (a potent anti-progestin).…”
Section: Functional Relevance Of Pr Expression During Mes Cell Differmentioning
confidence: 99%